2017
DOI: 10.1007/s10863-016-9693-5
|View full text |Cite
|
Sign up to set email alerts
|

Energetic, oxidative and ionic exchange in rat brain and liver mitochondria at experimental audiogenic epilepsy (Krushinsky–Molodkina model)

Abstract: The role of brain and liver mitochondria at epileptic seizure was studied on Krushinsky-Molodkina (KM) rats which respond to sound with an intensive epileptic seizure (audiogenic epilepsy). We didn't find significant changes in respiration rats of brain and liver mitochondria of KM and control rats; however the efficiency of АТР synthesis in the KM rat mitochondria was 10% lower. In rats with audiogenic epilepsy the concentration of oxidative stress marker malondialdehyde in mitochondria of the brain (but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In the pilocarpine-induced model of Status Epilepticus (SE), a reduction of GSH is observed (41, 42), leading to excessive lipid peroxidation in the hippocampus and cortex (43); in kainic acid-induced seizures, there is an overproduction of ROS associated with mitochondrial dysfunction and calcium overload mediated by excessive glutamate receptor activation, leading to the damage of cell structures and alterations including hippocampal lipids and proteins (44). In audiogenically susceptible strains such as GEPRs (acute seizures), a breakdown in hippocampal glutathione peroxidase (GPx) activity has been described, with a decrease in GSH/GSSG ratio (40, 45), while in the whole brain of the Krushinsky-Molodkina (KMs) rat an increased ROS generation by mitochondrial complex I dysfunction was observed (46).…”
Section: Discussionmentioning
confidence: 99%
“…In the pilocarpine-induced model of Status Epilepticus (SE), a reduction of GSH is observed (41, 42), leading to excessive lipid peroxidation in the hippocampus and cortex (43); in kainic acid-induced seizures, there is an overproduction of ROS associated with mitochondrial dysfunction and calcium overload mediated by excessive glutamate receptor activation, leading to the damage of cell structures and alterations including hippocampal lipids and proteins (44). In audiogenically susceptible strains such as GEPRs (acute seizures), a breakdown in hippocampal glutathione peroxidase (GPx) activity has been described, with a decrease in GSH/GSSG ratio (40, 45), while in the whole brain of the Krushinsky-Molodkina (KMs) rat an increased ROS generation by mitochondrial complex I dysfunction was observed (46).…”
Section: Discussionmentioning
confidence: 99%
“…Characteristically, this decrease was partially compensated in the "0" rats (Supplementary Figure 2). It was previously shown that KM rats demonstrated reduced ATP production and increased H 2 O 2 levels in the brain and liver compared with W rats (Venediktova et al, 2017). In our study, KM rat mitochondrial disorders also induced an increase in the expression of a number of genes that positively regulate apoptosis (Figure 4).…”
Section: Discussionsupporting
confidence: 72%
“…This could also signify that some early mutation event occurred rather frequently in rodent brain which affect brain development as a whole, but which is compatible with normal development and function in the absence of sound. This cautious assumption is confirmed by the finding of differences in mitochondrial function in KM rats vs Wistar as well (23). Finally, the KM strain showed the significant decrease in the expression of the Msh3 gene (fig.…”
Section: Resultsmentioning
confidence: 58%